Modeling of blood clot removal with aspiration Thrombectomy devices - G. Romero; C. Talayero; G. Pearce; J. Wong (Journal of Mechanical Engineering and Sciences, 2020)
Thrombectomy by aspiration is a highly effective method of accomplishing vessel recanalization. This study aims to obtain a mathematical model that allows the prediction of the dynamic response of a thrombus in response to different suction conditions, in order to avoid potential damage or the breakage of the clot during the interventional procedure. Virtual computing models have been created using Bond-Graph data and mass-spring Multi-Degree of Freedom equations. The model allows the use of tensile and torsion loads that could potentially be generated by the suction pressure together with different catheter geometries. The stress generated in the clot depends on its length and on its stiffness. The results obtained with the mathematical model are validated with a Finite Element Method (FEM) model, shows good agreement in terms of stress and elongation values. The results are consistent with previous Bond Graph models which indicated that the forces needed to extract a blood clot from an artery in in-vitro experiments are within the range used experimentally (~40-90 kPa). Qualitative experiments are undertaken with 3D printed scale prototypes and gelatin. The results are consistent with Computer Fluid Dynamic (CFD) simulations.